(untitled) (Biocenosis, 2022)
As one of its major tasks, Distance State University (UNED) aims at strengthening the correlation between teaching, research, and extension. The objective of this study is to analyze the personnel’s perceptions regarding academic processes related to ecological restoration through the application of 16 surveys to professors of the career of Natural Science Teaching (PECN) and Natural Resource Management (MARENA) program. The study shows that 59% of the teachers lack important information about the subject; therefore, they require training to enhance their scientific skills and biology knowledge, as well as collaborative work associated to ecological restoration. The former requires developing specific didactic strategies to enable opportunities for exchange spaces so as to improve the ecosystems in general.